Studies on the Effect of Waist Movement on the Ski Turn - SAKURAI, Yuki; IWAMI, Takehiro; NAGAI, Chikara; DOKI, Hitoshi (Journal of Ski Science, 2004)
The engineering approach is one of the most important methods for contributing to the sports research. In the analysis of the ski turn, the mechanism of the physical exercise has been analyzed from the viewpoint of dynamics. A carving ski is rapidly spreading in recent years for the high skiing performance. The skiing style has also changed in order to sufficiently utilize the performance of the carving ski. Although it has been pointed out that the difference of the inclination angle of pelvis affects the skiing, there is no research that quantitatively evaluated the difference. We already developed the measurement system that simultaneously could measure the attitude of the skier and the reaction forces from the snow surface under skiing. This measurement system was improved in order to measure the inclination angle of pelvis. In this study, we tried to evaluate quantitatively the effect of inclination of pelvis on the ski turn using this measurement system. It was found that the forward tilting attitude of the pelvis expanded the range of motion of hip joint and that the hip joint was used effectively in the ski turn. Our evaluation method will be useful for not only development of the ski goods but also improvement of training and guidance methods in skiing.